Möglichkeiten und Grenzen nationaler Stadtpolitik — Eine politikwissenschaftliche Perspektive - Bogumil, Jörg; Grohs, Stephan; Reiter, Renate (Raumforschung und Raumordnung | Spatial Research and Planning, 2008)
The article deals with the leeway of integrated national urban policies. The competencies and options of the German federal government concerning the city regions are put in comparative perspective. Experiences with programmes of national urban policies are resumed for identifying pivotal problems. Restricted competencies and a lack of coordination in federal government cause a sceptical view on the possibility of an integrated approach of urban policy “from above”. Without neglecting the innovative character of federal pilot projects, a strengthening of local competencies and their room for manoeuvre is identified as a more important policy approach.